Synthetic Biodegradable Polymers as Adsorbents of Dyes - Aryanfar, Yashar; García-Alcaraz, Jorge Luis; ourbakhsh Sadabad, Arash; Nami Khalilehdeh, Mahdi; Kecebas, Ali; Mirzaei, Fathemeh; Blanco Fernandez, Julio; Awad, Mohamed (Elsevier, 2024)
https://www.sciencedirect.com/science/article/abs/pii/B9780323954860001150?via%3Dihub